UPAYA PENANGANAN NYERI HAID (DYSMENORRHEA) DENGAN KOMPRES HANGAT REBUSAN JAHE - Diah Ayu Fatmawati; Siti Muniroh; Musnitarini Ramadhani (Universitas Pesantren Tinggi Darul Ulum, 2018)
ABSTRACTMenstrual pain (dysmenorrhea) is painful during menstrual periods or during menstruation to make the woman is not working and must sleep. Pain along with nausea, headache, feeling fainted, irritability. The purpose of this study was to determine the influence of warm compresses of ginger stew to decrease menstrual pain (dysmenorrhea). This research uses Quasy Experiment design pretest-posttest design using Purposive Sampling technique. The subjects in this study were female students in Sulaiman-Bilqis Darul 'Ulum dormitory as many as 38 respondents who meet the inclusion and exclusion criteria. Data retrieval was obtained using observation. Data were analyzed using Paired Sample T-Test and Independent Sample T-Test with significance level ≤0.05. The results showed the pain intensity before treatment in both groups was comparable p> 0.05. The intensity of menstrual pain decreased significantly after the treatment of 6.42-3.21 in the warm ginger stew compress group, and from 6.84 to 5.63 in the warm compress group (p <0.05). Intensity of menstrual pain (dysmenorrhea) after treatment there was no significant difference between warm ginger stir compress group and warm compress (3.21 ± 2.070 vs. 5.63 ± 2.314). Group of warm ginger stew compresses decreased the level of pain higher than the control group with warm compress only. From result of paired t-test in treatment group obtained result of P-value = 0,000. Warm compresses of ginger stew and warm compresses decrease menstrual pain (dysmenorrhea), so it can be used as an alternative or nonfakmakologi way in reducing the intensity of menstrual pain (dysmenorrhea). Keywords: painful menstruation (dysmenorrhea), warm compresses, red ginger.